Discovery of Novel Pleuromutilin Derivatives as Potent Antibacterial Agents for the Treatment of MRSA Infection - Han-Qing Fang; Jie Zeng; Shou-Kai Wang; Xiao Wang; Fang Chen; Bo Li; Jie Liu; Zhen Jin; Ya-Hong Liu; You-Zhi Tang (Molecules, 2022)
A series of novel pleuromutilin derivatives containing nitrogen groups on the side chain of C14 were synthesized under mild conditions. Most of the synthesized derivatives displayed potent antibacterial activities. Compound 9 was found to be the most active antibacterial derivative against MRSA (MIC = 0.06 μg/mL). Furthermore, the result of time-kill curves showed that compound 9 had a certain inhibitory effect against MRSA in vitro. Moreover, according to a surface plasmon resonance (SPR) study, compound 9 (KD = 1.77 × 10−8 M) showed stronger affinity to the 50S ribosome than tiamulin (KD = 2.50 × 10−8 M). The antibacterial activity of compound 9 was further evaluated in an MRSA-infected murine thigh model. Compared to the negative control group, tiamulin reduced MRSA load (~0.7 log10 CFU/mL), and compound 9 performed a treatment effect (~1.3 log10 CFU/mL). In addition, compound 9 was evaluated in CYP450 inhibition assay and showed only moderate in vitro CYP3A4 inhibition (IC50 = 2.92 μg/mL).